Analysis of Production Sensitiveness and Price of Seaweed (Kappaphycus Alvarezi) at Cultivater Level - Darmawati, Darmawati; Nursidi, Nursidi; Nurbaya, Nurbaya; Dananjaya, Wayan Kantun (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Seaweed is an export commodity so it requires continuous production to ensure the sustainability of raw materials. This study aims to analyze the sensitivity of seaweed production and prices at the cultivator level in Nunukan District, North Kalimantan. This research is classified as a type of quantitative research with observation methods through interviews and distribution of questionnaires to seaweed cultivators. The variables analyzed are costs and income at the cultivator level, through a farmer's financial feasibility analysis based on the parameters NPV, IRR, Net B/C. Respondents in this study were seaweed cultivators. The results showed that the average dry seaweed production in 1 year was 16,424 kg with an average price of Rp. 20,667 and annual revenue of Rp. 337,683,200. This can be seen from the NPV value obtained, which is Rp. 317,970,947, - at the current bank interest rate of 7%. While the Net B/C obtained is 2.4, the IRR value is 46.0%, and the Payback Period is 8 months 15 days, as an indicator that seaweed cultivation is feasible to develop. Based on sensitivity analysis data for seaweed cultivation, if with constant production, production costs increase by 5%, an NPV value of 253,390,476 is obtained, a B/C ratio of 2.1 with an IRR of 36.98%. The NPV and B/C ratio parameters show that this business is feasible to continue and in terms of IRR the business has a sustainable opportunity.